Curcumin promotes spermatogenesis in mice with cryptorchidism by regulating testicular protein O-GlcNAcylation - Wang, Zhen; Chen, Fujia; Li, Yun; Liu, Chaoying; Wang, Lizhen; Shao, Weilun; Lu, Zhen; Hu, Li; Li, Longxuan; Wang, Yue; Lin, Jinyang; Yu, Yaxuan; et al. (Frontiers in Endocrinology, 2025)
IntroductionCurcumin has garnered increasing attention in male reproductive research due to its potential anti-infertility properties. This study aimed to explore the protective effects of curcumin on spermatogenesis impairment in mice with cryptorchidism and to elucidate the underlying mechanisms.MethodsA total of 56 male Kunming mice aged 10 to 15 days were randomly assigned to different groups, including a control group (BO) and a cryptorchid group with five curcumin treatment groups (CC25, CC50, CC100, CC200, and CC300) receiving varying doses of curcumin (25, 50, 100, 200, and 300 mg/kg, respectively). After five weeks of treatment, evaluations based on organ coefficients, sperm count detection, testicular pathology analysis, and hormone level assessments determined the most effective curcumin dosage.Results and disccusionThe findings indicated that cryptorchidism had a detrimental impact on reproductive function, evident by decreased testicular coefficient, cessation of sperm production, abnormal testicular tissue morphology, and hormonal imbalances. Curcumin treatment mitigated these abnormalities, with the most significant improvement observed at a dosage of 100 mg/kg, without substantial adverse effects on other organs. Mechanistic studies revealed that cryptorchidism reduced testicular protein O-GlcNAcylation levels, while curcumin supplementation effectively increased this modification in a dose-dependent manner. Molecular docking and UDP-GlcNAc analyses further demonstrated that curcumin restores O-GlcNAcylation homeostasis by inhibiting OGA via high-affinity binding and enhancing OGT activity through substrate accumulation, synergistically rebalancing O-GlcNAcylation dynamics. This study uncovers a novel mechanism by which curcumin facilitates spermatogenesis through the regulation of testicular protein O-GlcNAcylation, providing a significant theoretical foundation for its utilization in male reproductive health.